INCORPORATING FREE WRITING TECHNIQUE IN ENGLISH CLASS: A CLASS ROOM ACTION RESEARCH TO IMPROVE STUDENTS’ WRITING ABILITY - Dunifa, La; Jaida (English Education Journal, 2025)
This classroom action research aims to assist students overcome their writing problems and enhance the quality of their writing using freewriting technique. Specifically, the research aimed to address two research questions: (1) Is there any improvement on students’ writing quality through the implementation of free writing technique? (2) How is students’ perception toward the implementation of free writing technique? The research was carried out at SMPN 48 Buton during the even semester of academic-year 2023/2024 with 25 participants. The study was conducted in two cycles, with three steps in each cycle: preparation, implementation, and observation. Writing tests were applied to collect data on students’ writing performance, and students’ perceptions toward the application of freewriting technique were gathered through interview. The data were analyzed quantitatively and qualitatively. The results of the research shows that: (1) students’ writing quality is successful to be improved in two cycles of the implementation of freewriting technique, and (2) in general, students regard that their writing quality improve since freewriting technique is motivated, and the techique is also effective to reduce their writing anxiety. This implies that freewriting technique is significantly effective to improve students’ writing quality.